Healthy eating for lower blood pressure : For the first time, a chef and a nutritionist have teamed up to inspire you with over 100 delicious recipes - Gayler, paul; Heiser, Gemma (Kyle Cathie, 2010)
Healthy eating plays a vital part in reducing high blood pressure - meals that are rich in wholegrains, fruits, vegetables, and dairy and low on saturated fat can help you avoid, delay or reduce the need for medication. This book features over 100 recipes for breakfasts, lunches, snacks and suppers that contain as much nutrition as they do flavor